Cerebrovascular complications of coccidioidomycosis meningitis: Case report and systematic review. (October 2020) - Phelps, Ryan R.L.; Lu, Alex Y.; Lee, Anthony T.; Yue, John K.; Winkler, Ethan A.; Raygor, Kunal P.; Oh, Taemin; Barkovich, Matthew J.; Hollander, Harry
Highlights: Coccidioidomycosis meningitis can cause aneurysms, hemorrhage, and vasospasm. Coccidioidomycosis-induced cerebral aneurysms are surgically/endovascularly treatable. Coccidioidomycosis-induced intracranial hemorrhage has a mortality rate of over 80%. Coccidioidomycosis-induced cerebral vasospasm is treatable with balloon angioplasty. Coccidioidomycosis-induced transient ischemic attacks are medically treatable. Abstract: Coccidioidomycosis exposure is common in the southwest United States and northern Mexico. Dissemination to the meninges is the most severe form of progression. Although ischemic strokes are well-reported in these patients, other cerebrovascular complications of coccidioidomycosis meningitis (CM), as well as their treatment options and outcomes, have not been systematically studied. We present a uniquely severe case of CM with several cerebrovascular complications. We also systematically queried PubMed and EMBASE databases, including articles published before April 2020 reporting human patients with CM-induced cerebrovascular pathology other than ischemic infarcts. Sixteen articles met inclusion criteria, which describe 6 patients with aneurysmal hemorrhage, 10 with non-aneurysmal hemorrhage, one with vasospasm, and one with transient ischemic attacks. CM-associated aneurysms invariably presented with hemorrhage. These were universally fatal until the past decade, when advances in surgical clipping and/or combined surgical and endovascular treatment have improved outcomes. We found that non-aneurysmal intracranial hemorrhages were limited to male patients, involved a diverse set of intracranial vasculature, and had a mortality rate surpassing 80%. Vasospasm was reported once, and was treated with percutaneous transluminal angioplasty. Transient ischemic attacks were reported once, and were successfully treated with fluconazole and dexamethasone. This review suggests that CM can present with a wide array of cerebrovascular complications, including ischemic infarcts, aneurysmogenesis, non-aneurysmal intracranial hemorrhage, vasospasm, and transient ischemic attacks. Mortality has improved over time due to advances in surgical and endovascular treatment modalities. The exception is non-aneurysmal intracranial hemorrhage, which remains associated with high mortality rates and few targeted therapeutic options.